Street Pastors: on security, care and faith in the British night-time economy - Steden, Ronald van (European journal of criminology, 2018)
This paper presents a study of Street Pastors in Cardiff, the capital city of Wales. Street Pastors are Christian volunteers who look after vulnerable people in the night-time economy. In this manner, they provide securitas through empathy and care. The motives of Street Pastors for engaging with partygoers are multi-layered, but their personal faith appears to be a key explanation. A certain kind of orthodox certitudo – of being safe in, and saved by, a higher power – gives the pastors their strength to go out on the street, face the unknown and feel compassion for their fellow citizens. As such, both ‘securitas’ and ‘certitudo’ highlight positive (that is, constitutive) connotations of safety and security not commonly heard in the criminological literature.